Women's health needs in patient education - Redman, Barbara Klug (Focus on women, 1999)
"The goal of this book is to fill the many gaps that health care providers face when helping women learn self care and prevention skills. Special attention is paid to minority status, low literacy, and elderly women who may have fewer opportunities to find health information independently."--BOOK JACKET.